Physionomy of the Bebegig Sukamantri Mask in Indonesian Sundanese Culture - Putra, Edi Setiadi (International Journal Ethnic, Racial and Cultural Heritage, 2025)
Sukamantri Village in West Java, Indonesia, has a community that is very enthusiastic in developing the Bebegig Sukamantri art. On December 20, 2016, the Sukamantri District community successfully presented a parade of 320 bebegig accompanied by 604 kolotok dancers, which was recorded as the largest number according to the Original Indonesian Record (ORI). In 2018, it was designated as an Intangible Cultural Heritage by the Indonesian Ministry of Education and Culture. The attraction of Bebegig Sukamantri lies in the design of the spooky and very large bebegig mask with forest plant attributes. Bebegig dancers wear clothes made of palm fiber, the crown of the mask is made of flowers and forest leaves. The purpose of this study is to determine the meaning contained in the design of the Bebegig Sukamantri mask, as well as what local wisdom is contained in it. The research method used is an interpretation study of the visual structure and appearance of the mask, through an analysis of similarities in shape and differences in appearance. The results of the study show that the Bebegig Sukamantri Mask is generally made without a prior design process, and consists of three large groups based on the character category and the accompanying attribute signs. The unique appearance of the Bebegig Sukamantri Mask is influenced by the face of Batara Kala with detailed attributes related to three groups of ancient Sundanese society, namely Rama-Resi-Ratu, who have a protective god, called Denawa-Ditya-Rakhasa, as described in Sanghyang Siksa Kanda ng Karesian, in the 15th century AD. The physiognomy of the mask is very interesting, because it consists of various different characters but has a strong and sustainable Sundanese philosophical content.